Exposure of α-Synuclein Aggregates to Organotypic Slice Cultures Recapitulates Key Molecular Features of Parkinson's Disease - Moudio, Serge; Rodin, Fredrik; Albargothy, Nazira Jamal; Karlsson, Urban; Reyes, Juan F.; Hallbeck, Martin (Frontiers in Neurology, 2022)
The accumulation of proteinaceous deposits comprised largely of the α-synuclein protein is one of the main hallmarks of Parkinson's disease (PD) and related synucleinopathies. Their progressive development coincides with site-specific phosphorylation, oxidative stress and eventually, compromised neuronal function. However, modeling protein aggregate formation in animal or in vitro models has proven notably difficult. Here, we took advantage of a preclinical organotypic brain slice culture model to study α-synuclein aggregate formation ex vivo. We monitored the progressive and gradual changes induced by α-synuclein such as cellular toxicity, autophagy activation, mitochondrial dysfunction, cellular death as well as α-synuclein modification including site-specific phosphorylation. Our results demonstrate that organotypic brain slice cultures can be cultured for long periods of time and when cultured in the presence of aggregated α-synuclein, the molecular features of PD are recapitulated. Taken together, this ex vivo model allows for detailed modeling of the molecular features of PD, thus enabling studies on the cumulative effects of α-synuclein in a complex environment. This provides a platform to screen potential disease-modifying therapeutic candidates aimed at impeding α-synuclein aggregation and/or cellular transmission. Moreover, this model provides a robust replacement for in vivo studies that do not include behavioral experiments, thus providing a way to reduce the number of animals used in an accelerated timescale.